The impact of the COVID-19 pandemic on local government cultural institutions – the productivity of theatres - Gałecka, Małgorzata; Smolny, Katarzyna (Wydawnictwo Uniwersytetu Wrocławskiego, 2023)
The new reality has led us to investigate the changes in productivity in public cultural institutions. The research describes the pandemic period in the theatre sector. We are investigating whether productivity changes occurred and which indicator affected them. We hypothesize that the productivity index in 2020 was most dependent on the technological change. We use the Malmiqusit index to show changes in productivity between 2011–2020. Our results seem to fully reflect the pandemic reality when the technological factor was of crucial importance. However, we would like to point out that technological growth alone does not bring satisfactory results in terms of productivity growth. Properly coordinated actions are also necessary for the broadly understood activities of the theatre. Depending on the organization, the impact of digital technologies may differ. The use of technology alone is not sufficient to achieve an increase in the productivity of the organization.
Keywords: performance art organizations; theatre; technical efficiency; Malmquist index value; total factor productivity